1981
DOI: 10.1128/iai.31.1.362-370.1981
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of Brucella abortus lipopolysaccharides

Abstract: Purified lipopolysaccharide (LPS) from smooth (S) and rough (R) strains of Brucella abortus and lipid A isolated from S-LPS by mild acid hydrolysis were examined in several assays of biological activity. Brucella Sand R-LPSs and Brucella lipid A activated the complement cascade. Previously reported mitogenic activation by Brucella LPSs of spleen cells from endotoxin-resistant C3H/ HeJ mice was confirmed and also produced by isolated Brucella lipid A. Mitogenicity was not inhibited by polymyxin B, and amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 22 publications
6
56
1
3
Order By: Relevance
“…Lipopolysaccharide contents of CYT and LPSfree CYT fractions were determined by Limulus lysate gelation activities (LLGA) as described by Sullivan and Watson [12] using E. coli LPS as standard. Brucella abortus S-LPS contents were estimated using the ratio reported by Moreno et al [13] between E. coli and B. abortus LPS gelating activities. This immune adsorption reduced the LPS concentration from 10 mg ml-1 in CYT to 9 × 10 3 mg ml-1 in LPS-free CYT [8].…”
Section: Determination Of Igg Anti-lps Antibodiesmentioning
confidence: 99%
“…Lipopolysaccharide contents of CYT and LPSfree CYT fractions were determined by Limulus lysate gelation activities (LLGA) as described by Sullivan and Watson [12] using E. coli LPS as standard. Brucella abortus S-LPS contents were estimated using the ratio reported by Moreno et al [13] between E. coli and B. abortus LPS gelating activities. This immune adsorption reduced the LPS concentration from 10 mg ml-1 in CYT to 9 × 10 3 mg ml-1 in LPS-free CYT [8].…”
Section: Determination Of Igg Anti-lps Antibodiesmentioning
confidence: 99%
“…Another study has suggested that LPS can be exocytosed in culture supernatants after bacterial processing (Duncan et al ., 1986). Intracellular Proteobacteria such as Bartonella , Coxiella , Brucella , Chlamydia , Legionella , Porphyromonas and Rickettsia have unique properties, which can be attributed to distinct LPS structures (Moreno et al ., 1981;Neumeister et al ., 1998;Moriyon, 2004;Zahringer et al ., 2004). In contrast to the LPS of enterobacteria, the modified lipid A of the intracellular Proteobacteria confers low endotoxicity, deficient host cell activation and resistance to degradation by macrophages (Erridge et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the O antigen of Brucella LPS is a homopolymer of perosamine (4,6dideoxy-4-formamido-d-mannopyranosyl) (3,27,37). The biological activities such as cytokine production and lethality of S-LPS and rough types of LPS (R-LPS) from various Brucella strains are reported to be lower than those of enterobacterial LPS (4,14,25,29). The lower endotoxicity seems to be responsible for the unique lipid A structure of Brucella LPS.…”
mentioning
confidence: 99%